Targeted capture enrichment assay for non-invasive prenatal testing of large and small size sub-chromosomal deletions and duplications. - Maria C Neofytou; Kyriakos Tsangaras; Elena Kypri; Charalambos Loizides; Marios Ioannides; Achilleas Achilleos; Petros Mina; Anna Keravnou; Carolina Sismani; George Koumbaris; Philippos C Patsalis (PLoS ONE)
Noninvasive prenatal testing (NIPT) using whole genome and targeted sequencing has become increasingly accepted for clinical detection of Trisomy 21 and sex chromosome aneuploidies. Few studies have shown that sub-chromosomal deletions or duplications associated with genetic syndromes can also be detected in the fetus noninvasively. There are still limitations on these methodologies such as the detection of variants of unknown clinical significance, high number of false positives, and difficulties to detect small aberrations. We utilized a recently developed targeted sequencing approach for the development of a NIPT assay, for large and small size deletions/duplications, which overcomes these existing limitations. Artificial pregnancies with microdeletion/microduplication syndromes were created by spiking DNA from affected samples into cell free DNA (cfDNA) from non-pregnant samples. Unaffected spiked samples and normal pregnancies were used as controls. Target Capture Sequences (TACS) for seven syndromes were designed and utilized for targeted capture enrichment followed by sequencing. Data was analyzed using a statistical pipeline to identify deletions or duplications on targeted regions. Following the assay development a proof of concept study using 33 normal pregnancies, 21 artificial affected and 17 artificial unaffected pregnancies was carried out to test the sensitivity and specificity of the assay. All 21 abnormal spiked-in samples were correctly classified as subchromosomal aneuploidies while the 33 normal pregnancies or 17 normal spiked-in samples resulted in a false positive result. We have developed an NIPT assay for the detection of sub-chromosomal deletions and duplications using the targeted capture enrichment technology. This assay demonstrates high accuracy, high read depth of the genomic region of interest, and can identify deletions/duplications as small as 0.5 Mb. NIPT of fetal microdeletion/microduplication syndromes can be of enormous benefit in the management of pregnancies at risk both for prospective parents and health care providers.